Age‐ and Procedure‐Specific Differences of Epidural Analgesia in Children—A Database Analysis. Issue 3 (19th January 2015) - Schnabel, Alexander; Thyssen, Navina M.; Goeters, Christiane; Zheng, Hua; Zahn, Peter K.; Van Aken, Hugo; Pogatzki‐Zahn, Esther M.
Abstract: Objective: Several audits demonstrated the safety of epidural catheters in children undergoing surgery. Within the present data analysis, we investigated whether older compared with younger children and children with specific types of surgical procedures might report higher pain scores. Methods: All children (0–18 years) treated with an epidural catheter for postoperative pain treatment between March 2006 and December 2010 at the University Hospital of Muenster (Germany) were included. Postoperative pain intensities, the number of patients with the need for additional opioids, and catheter‐related complications during placement and early postoperative period were analyzed. Results: Data of 830 children receiving an epidural catheter (Nthoracic/lumbar = 691; Ncaudal = 139) were included. Adolescents (12–18 years) treated with a thoracic/lumbar epidural had higher pain scores compared with preschoolers and school children ( P < 0.05) and received less additional systemic opioids ( P < 0.001). In the thoracic/lumbar epidural group, children undergoing spine surgery showed comparable pain scores with those undergoing thoracic procedures, but had higher pain scores than children undergoing abdominal or extremity surgery ( P < 0.05). However, children undergoing spine surgery received less additional opioids, but this was only significant at the first postoperative day ( P = 0.032). Conclusions: This database analysis demonstrated that older children and children undergoing thoracic or spine surgery reported significant higher pain scores most likely because they received less additional opioids. Therefore, a more "aggressive" pain treatment (including opioids on demand under appropriate monitoring) might further improve postoperative care.